2012
DOI: 10.1128/jvi.06913-11
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus 1 VP22 Regulates Translocation of Multiple Viral and Cellular Proteins and Promotes Neurovirulence

Abstract: Herpes simplex virus 1 (HSV-1) protein VP22, encoded by the UL49 gene, is a major virion tegument protein. In the present study, we showed that VP22 was required for efficient redistribution of viral proteins VP16, VP26, ICP0, ICP4, and ICP27 and of cellular protein Hsc-70 to the cytoplasm of infected cells. We found that two dileucine motifs in VP22, at amino acids 235 and 236 and amino acids 251 and 252, were necessary for VP22 regulation of the proper cytoplasmic localization of these viral and cellular pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 68 publications
2
51
0
Order By: Relevance
“…This may be because other HSV-1 factors also regulate ICP4 localization during infection and can compensate for the ICP27 alteration in K2F1. Consistent with this, a recent study showed that HSV-1 tegument protein VP22 promotes the cytoplasmic localization of ICP4 (58).…”
Section: Discussionsupporting
confidence: 69%
“…This may be because other HSV-1 factors also regulate ICP4 localization during infection and can compensate for the ICP27 alteration in K2F1. Consistent with this, a recent study showed that HSV-1 tegument protein VP22 promotes the cytoplasmic localization of ICP4 (58).…”
Section: Discussionsupporting
confidence: 69%
“…The more striking feature in the present study was that the phosphorylation, as well as the enzymatic activity, of vdUTPase played no role in viral replication and pathogenicity in the eyes and vaginas of mice following ocular and vaginal inoculation, respectively. To our knowledge, HSV proteins or their domains critical for viral replication and virulence in the CNS of mice following intracranial inoculation are, in almost all cases, also involved in pathogenicity in peripheral sites, such as eyes and vaginas, following peripheral (ocular and vaginal) inoculation (7,10,11,15,27,41,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59). Therefore, this phosphorylation reaction, which promoted the vdUTPase activity, is a unique indication of a specific mechanism involved in HSV-1 replication and virulence in and replication in mice.…”
Section: Fig 5 Effect Of Mutations In Vdutpase or The Kinase-dead Mutmentioning
confidence: 99%
“…Commercial mouse monoclonal antibodies to Myc (PL14; MBL), ␣-tubulin (DM1A; Sigma), ICP0 (1112; Goodwin Institute), ICP4 (58S; ATCC), VP5 (3B6; Virusys), gB (H1817; Virusys), gD (DL6; Danta Cruz Biotechnology), gH (52-S; ATCC), gC (H1A022; Virusys), gG (7F5; Virusys), and gE (9H3; Abcam) and commercial rabbit polyclonal antibodies to VP23 (CAC-CT-HSV-UL18; CosmoBio) and UL11 (CAC-CT-HSV-UL11; CosmoBio) were used. Rabbit polyclonal antibodies to UL51, UL14, UL7, UL31, UL34, VP26, UL41, UL46, VP13/ 14, VP16, VP22, UL50, Us3, and Us9, a mouse monoclonal antibody to UL13, and a mouse polyclonal antibody to gN were described previously (7,26,35,(38)(39)(40)(41)(42). Rabbit polyclonal antibody to gM (43) was kindly provided by J. Baines.…”
Section: Cells and Virusesmentioning
confidence: 99%